INDONESIAN WARSHIP HISTORY INFORMATION SYSTEM OF INDONESIAN FLEET BASED ON WEB - Zainal Syahlan; Khairul Huda; M Syaifi; Edy Widodo (JOURNAL ASRO, 2019)
The development of information technology also developed in line with thedevelopment of human civilization. The development of information technology is veryhelpful, one of which is the internet. The use of the internet has developed into anappropriate means to convey information that is fast, effective and accurate. Submissionof information is not limited to all soldiers and the general public by utilizing technologicalfacilities, namely websites. In conveying the history of Indonesia Warship Raden EddyMartadinata 331 and Indonesia Warship I Gusti Ngurah Rai 332 are still stored in the formof documents on a computer and are still printed in the form of sheets of paper. Inconveying the history of Indonesia Warship, it must be developed further to conveyinformation in the current era. Historical research that executive focuses on the past. Sofar, information on the Indonesia Warship Indonesia Warship's historical informationsystem Raden Eddy Martadinata - 331 and Indonesia Warship I Gusti Ngurah Rai - 332on the web-based Indonesian Armed Forces fleet are still in print. besides usinginformation books, then try to make other alternatives by creating a website, besides thatmembers are expected to access information easily and efficiently. With theineffectiveness in managing Indonesia Warship Indonesia Warship historical data RadenEddy Martadinata - 331 and Indonesia Warship I Gusti Ngurah Rai - 332, a design of theIndonesia Warship historical information system was built in the web-based IndonesianArmada fleet which aims to facilitate the process of Indonesia Warship history search.PHP as a programmer and MySQL as the database.Keywords: Website-Based Indonesia Warship History Information System. PHP MySQL.